Báo cáo tiếp thu, giải trình ý kiến của Ủy ban Thường vụ Quốc hội đối với Dự án Luật Căn cước - Chính phủ (2023)
Toàn văn Báo cáo tiếp thu, giải trình ý kiến của Ủy ban Thường vụ Quốc hội đối với Dự án Luật Căn cước.